St. Vincent and the Grenadines : pulling the kite back up in the air. - DE BACKER, Roger (1994)
Presents an overview of the economic situation in St. Vincent and the Grenadines. Describes the land reform programme, and points out that the agricultural diversification exercise is also tied to this programme, while tourism development would be complementary to agricultural diversification.